Neuro-Metabolic Disparity Model (NMDM): A Theoretical Framework for Understanding Cognitive Decline in Underrepresented Populations - Suliyat Abiodun Aremu (My University, 2025)
Global disparities in brain and mental health are not solely a consequence of genetic or neurobiological factors. Instead, they reflect the cumulative effects of metabolic dysfunction, chronic psychosocial stress, environmental exposures, and systemic inequities that disproportionately affect underrepresented populations. This theoretical paper introduces the Neuro-Metabolic Disparity Model (NMDM), an integrative framework that situates cognitive decline at the intersection of biological and social adversity. Drawing from syndemic theory, population neuroscience, and the exposome framework, the NMDM emphasizes the synergistic effects of metabolic disorders and structural disadvantage on brain aging. The model outlines four core components, embodied biological factors, embedded social determinants, neurocognitive vulnerability pathways, and population-level context—and proposes neuroinflammation, oxidative stress, and blood-brain barrier disruption as key mediators. Cultural resilience and social support are considered potential buffers. This framework provides a foundation for more inclusive and equity-focused neuroscience research, with implications for global brain health policy and practice.
Keywords: brain health; mental health; disparity; cognitive decline; population neuroscience; syndemics; exposome; metabolic dysfunction